Environmental Disclosure Practice of Nepalese “A” Listed Companies (The Batuk, 2019)
The disclosure of environment related information is an inevitable component of corporate social reporting paradigm. Due to growing awareness to protect environment, firms around the globe are supposed to be involved in activities in protection and betterment of environment. The stakeholder theory suggests for considering stakeholders while making corporate strategies and reporting them information including initiations done in behalf of environmental responsibility. This paper attempts to study the corporate environmental disclosure practice of selected 45 NEPSE “A” listed companies of Nepal. Different ten measures of this environmental theme were considered for analysis. Content analysis was applied to know the extent of disclosure practice of the companies and variance test to examine variations in environmental disclosure of the companies within seven industry types. The result of content analysis indicated that disclosure status of environment information related items is very low and there is a significant variation in environmental disclosure practice of the companies across seven industry types.